Student Perceptions and Experiences of Internationalization Initiatives at Universitas YARSI - Arlinkasari, Fitri; Sakinah, Maulidiana; Wulandari, Ais; Badri, Afaq Zuhal Laili Rofi (KnE Social Sciences, 2025)
This qualitative research investigates students’ experiences and the perceptions of Universitas YARSI regarding the activities of university internationalization. Thematic analysis of a focus group discussion (FGD) with students of different faculties found that students predominantly perceive the internationalization process as an important step forward to improve the university’s global reputation and equip the students with important experience of working with international standards and practices. They view it as a way to access the opportunities of partnering with universities and researchers abroad. Nonetheless, students also stressed the substantial difficulties in continuing to participate in internationalization activities. Financial constraints, including travel and accommodation costs, emerged as a major obstacle. Furthermore, students indicated the desire to receive more support and recognition from the university on behalf of the internationalization project. Administratively and bureaucratically challenging factors, such as visas, were also reported as obstacles. To enhance internationalization efforts, students proposed several solutions. They requested more funding and backing from the university, such as financial aid. They further stressed the importance of increased communication and publicity of the university’s programs and resources through social media and the university’s website. In addition, it was pointed out that students thought it was important to simplify administrative procedures to make enrolment simpler, and that building partnerships for giving credit for study abroad was suggested. These results highlight the validity of the university’s internationalization efforts in relation to student needs and expectations. Through the recognition of the existing challenges and the application of the presented solutions, Universitas YARSI will be a better inclusive and supportive context to facilitate participation in internationalization activities to finally contribute to the vision of Universitas YARSI as a globally recognized institution.